The Influence of Brand Awareness, Influencers, and Product Quality on Purchase Intention of Skintific Skincare Products on Tiktok Social Media - Nisa Zhafira; Prasetyo Harisandi; Adibah Yahya (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the effect of brand awareness, influencers, and product quality on consumer purchase intention towards Skintific skincare products on TikTok social media. The research method used is quantitative with a descriptive approach, and data collection was carried out through questionnaires to Skintific product users. The results of the analysis using SmartPLS showed that the three independent variables had a significant effect on purchase intention, with a path coefficient value for brand awareness of 0.45 (p <0.01), for influencers of 0.35 (p <0.05), and for product quality of 0.40 (p <0.01). The R-Square value of 0.685 indicates that the model built has strong predictive ability, explaining 68.5% of the variance in purchase intention. This study provides policy implications that the integration of effective digital marketing strategies through TikTok by strengthening brand awareness, influencer collaboration, and improving product quality can increase purchasing interest and competitiveness of Skintific products. The contribution of this study not only enriches the literature on digital marketing but also provides practical guidance for marketers in designing more effective strategies.